1992
DOI: 10.1111/j.1699-0463.1992.tb00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the a antigen of the c proteins of group B streptococci (GBS) using a murine monoclonal antibody

Abstract: Bevanger, L., Iversen, 0-J. & Naess, A. I. Characterization of the a antigen of the c proteins of group B streptococci (GBS) using a murine monoclonal antibody. APMIS ZOO: 57-62, 1992.A murine monoclonal antibody raised against the a antigen of the group B streptococcal c proteins was analysed by immunofluorescence and whole-cell ELISA against a collection of 22 c proteinproducing GBS. All the strains showing fluorescence and reactivity in ELISA turned out to be a antigen-carrying strains as defined by polyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…Since alignments of sequences from the strain 515 whole-genome data and bca (C␣) sequences showed that the Alp1 and C␣ repeats were nearly identical, we tend to conclude that the Alp1/C␣ common site is located in the repeat region of the two Alps. Also the repeat region of the two protein antigens must be the targets for our anti-C␣ MAb which recognizes C␣ and Alp1 equally well (4,17). Over the years, this MAb has been used as a reagent in our laboratory to detect C␣, which has resulted in identification of Alp1-expressing isolates as C␣-expressing strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since alignments of sequences from the strain 515 whole-genome data and bca (C␣) sequences showed that the Alp1 and C␣ repeats were nearly identical, we tend to conclude that the Alp1/C␣ common site is located in the repeat region of the two Alps. Also the repeat region of the two protein antigens must be the targets for our anti-C␣ MAb which recognizes C␣ and Alp1 equally well (4,17). Over the years, this MAb has been used as a reagent in our laboratory to detect C␣, which has resulted in identification of Alp1-expressing isolates as C␣-expressing strains.…”
Section: Discussionmentioning
confidence: 99%
“…Antisera. Rabbit antisera and a murine anti-C␣ monoclonal antibody (MAb) were both raised against whole cells of GBS as previously described (2,4). The rabbit antisera were used unabsorbed or after cross-absorption as specified in Results.…”
Section: Methodsmentioning
confidence: 99%
“…Serotyping is based primarily on the GBS capsular polysaccharide antigens (CPA) designated Ia, Ib and II-VIII [4]. Sometimes, the CPA typing is supplemented by identification of serosubtype markers, strain-variable protein antigens such as c AE [5,6], c â [5], and the R proteins R1-R4 [7,8]. In addition, a number of other GBS protein antigens have been described, some of which showed cross-reactivity with classical R protein antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-c ␣ and anti-R4 monoclonal antibodies (MAbs) used in this study were those described previously (7,8). Polyclonal antibodies (PAbs) included antibodies raised in rabbits against whole cells of strains 335 and 65604, as described previously (8), and antisera raised against the purified c ␣ (7) and R4 (8) proteins.…”
Section: Methodsmentioning
confidence: 99%
“…These proteins include the c ␣ protein of the c protein fraction of GBS (7,10), the R1 to R4 proteins (8,13,18,23), protein Rib (31), a Rib-like protein (1), and c ␣ -like proteins (20,22). Large tandem repeats are additional characteristic features of these proteins (20,27,32), which harbor epitopes targeted by protective antibodies, according to experimental models (1,17,22,31).…”
mentioning
confidence: 99%